2008
DOI: 10.1007/s11135-008-9186-7
|View full text |Cite
|
Sign up to set email alerts
|

Performance improvement in new product development with effective tools and techniques adoption for high-tech industries

Abstract: New product development (NPD), Tools and techniques, Performance indicators, Effectiveness analysis model,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
62
0
14

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(84 citation statements)
references
References 39 publications
1
62
0
14
Order By: Relevance
“…they do not yet have a view of all phases of the product life cycle that is currently relevant to minimizing the environmental impact of the product. Kotler (1974), Bonsiepe (1978), Booz (1982), Saren (1984), Andreasen and Hein (1987), Park and Zaltman (1987), Suh (1988), Graf and Saguy (1991), Rosenthal (1992), Wheelwright and Clark (1992), Cooper (1993), Urban and Hauser (1993), Automotive Industry Action Group (1994), Fuller (1994), Ingle (1994), Nijssen and Lieshout (1995), Rudolph (1995), Roozenburg and Eekels (1995), McGrath (1996), Ertas and Jones (1996), Dickson (1997), Earle (1997), Prasad (1997), British Standards Institution (1997), Fleischer and Liker (1997), Peters et al (1999), Crawford and Benedetto (2000), Nwabueze and Law (2001), Kalpic and Bernus (2002), Tischner and Charter (2001) 2006), Thomke and Nimgade (2007), Ulrich and Eppinger (2007), Yeh et al (2010), Bigliard, Bottani and Rinaldi (2013) Social, economic, political, technological, environmental, and legal analysis (2) 10 (20%) Bonsiepe (1978), Graf and Saguy (1991), Rudolph (1995), McGrath (1996), ...…”
Section: Most Adopted Stages and Identification Of Environmental Concmentioning
confidence: 99%
“…they do not yet have a view of all phases of the product life cycle that is currently relevant to minimizing the environmental impact of the product. Kotler (1974), Bonsiepe (1978), Booz (1982), Saren (1984), Andreasen and Hein (1987), Park and Zaltman (1987), Suh (1988), Graf and Saguy (1991), Rosenthal (1992), Wheelwright and Clark (1992), Cooper (1993), Urban and Hauser (1993), Automotive Industry Action Group (1994), Fuller (1994), Ingle (1994), Nijssen and Lieshout (1995), Rudolph (1995), Roozenburg and Eekels (1995), McGrath (1996), Ertas and Jones (1996), Dickson (1997), Earle (1997), Prasad (1997), British Standards Institution (1997), Fleischer and Liker (1997), Peters et al (1999), Crawford and Benedetto (2000), Nwabueze and Law (2001), Kalpic and Bernus (2002), Tischner and Charter (2001) 2006), Thomke and Nimgade (2007), Ulrich and Eppinger (2007), Yeh et al (2010), Bigliard, Bottani and Rinaldi (2013) Social, economic, political, technological, environmental, and legal analysis (2) 10 (20%) Bonsiepe (1978), Graf and Saguy (1991), Rudolph (1995), McGrath (1996), ...…”
Section: Most Adopted Stages and Identification Of Environmental Concmentioning
confidence: 99%
“…Managers are thus under pressure to improve their companies'NPD performance. This requires more efficient and effective NPD processes-principally by avoiding wastage of resources on peripheral activities, changes, and reworks (Yeh, Pai and Yang, 2010). Furthermore, even within the NPD process, several activities (or phases) can be distinguished (concept design, engineering, testing and prototyping, production rump up, commercialization) which are different in terms of the above characteristics (time, level and type of risk, relevance of intangibles, distance from the market, etc.).…”
Section: New Product Development (Npd) Processmentioning
confidence: 99%
“…In theory and in practice, the definition of new product has been widely discussed among experts and scholars from different angles, including the view point of producers, consumers, and the product life cycle (Yeh, Pai and Yang, 2010). Levitt suggested that the new part of most new products is not pure innovation, but rather an imitation or improvement.…”
Section: New Product Development Performance (Npdp) Efficiencymentioning
confidence: 99%
See 1 more Smart Citation
“…We emphasise the alliance for the product development phase and consider the case in which firms continue to jointly develop a product but compete individually in the market (Amaldoss and Rapoport 2005). The modelling framework in this study differs from the conventional inter-firm collaborative product development studies focusing on technology assessment Qin 2006, Tseng et al 2007), design alternative selection (Shen et al 2008, Zhang andChu 2009), knowledge sharing and knowledge integration considerations (Hung et al 2008, Chen 2010 or tactical decisions (prices and quantities) (Hung et al 2007, Yeh et al 2009). …”
Section: Introductionmentioning
confidence: 99%